391 Positive surgical margin is an independent predictor of overall survival of patients with vulvar squamous carcinoma. (13th November 2020) - Nomura, H; Nishimura, M; Shimizu, Y; Omi, M; Netsu, S; Aoki, Y; Tanigawa, T; Kurita, T; Matoda, M; Okamoto, S; Omatsu, K; Kanao, H
Abstract : Background: It is uncertain whether curative surgical treatment or a less radical surgery with adjuvant treatment should be provided to preserve function in patients with vulvar squamous cell carcinoma (SCC) that is adjacent to the urethra, anus, and vagina. The aim of this study was to investigate the surgical margin in patients with vulvar SCC with regard to local recurrence and overall survival. Methods: Thirty-four patients were identified as having a diagnosis of vulvar SCC without distant metastasis. They had been treated surgically with curative intent at the Cancer Institute Hospital between May 1992 and January 2019. Clinical data were analyzed retrospectively. Results: Rates of 5-year local recurrence-free survival among patients with positive, <3-mm, <5-mm, <8-mm, and ≥8-mm surgical margins were 32%, 30.3%, 42.5%, 55.5%, and 73%, respectively. Rates of 5-year overall survival of patients with positive, <3-mm, <5-mm, <8-mm, and ≥8-mm surgical margins were 15.5%, 53.8%, 58.8%, 67.6%, and 83.3%, respectively. In the multivariable analysis, a tumor size of more than 2-cm (hazard ratio [HR] = 9.42, 95% confidence interval [CI] = 1.11–80.0) and a surgical margin of <3-mm (HR = 0.17, 95% CI = 0.042–0.70) were risk factors for local recurrence, and a tumor size of more than 2-cm (HR = 21.1, 95% CI = 2.00–222) and a positive surgical margin (HR = 0.084, 95% CI = 0.017–0.41) were significant risk factors for overall mortality. Conclusion: To improve the prognosis, thorough resection with an adequate surgical margin is needed.